Potential role and influence of zero tillage technology on energy saving in rice (Oryza sativa)- wheat (Triticurn aestivum) system - GUPTA, MEENAKSHI; BALI, AMARJIT S; SHARMA, SUSHIL; DIXIT, ANOOP K (The Indian Journal of Agricultural Sciences, 2011)
influence of zero-tillage technology on productivity and energy saving in rice-wheat system with two tillage methods, three fertility levels and five time of nitrogen application schedules for sustainable and ecofriendly agriculture. On the basis of two years field study it may be safely concluded that the zero tillage sowing was more remunerative in terms of labour, fuel and energy saving than the conventional method of sowing besides showing statistical parity for wheat grain yield. Zero tillage also recorded higher energy use-efficiency and energy productivity than conventional tillage method of sowing. Increasing fertility level from 75 to 125 per cent of recommended dose decreased energy use efficiency and energy productivity significantly. Application of nitrogen in three splits recorded higher energy use efficiency and energy productivity than treatments receiving nitrogen in two splits.